Solve the following exercise:

$\sqrt{9}\cdot\sqrt{3}=$

**Although** the square root of 9 is known (3) , in order to get __a single expression__ we will use the laws of parentheses:

So- in order to simplify the given expression **we will use two exponents laws**:

__A.__ Defining the root as a an exponent:

$\sqrt[n]{a}=a^{\frac{1}{n}}$__B.__ Multiplying different bases with the same power** (in the opposite direction)**:

$x^n\cdot y^n =(x\cdot y)^n$

__Let's start__ **by changing the **__square__ root into an exponent using the law shown in **A**:

$\sqrt{9}\cdot\sqrt{3}= \\
\downarrow\\
9^{\frac{1}{2}}\cdot3^{\frac{1}{2}}=$S__ince a multiplication is performed between two bases ____with the same exponent __we can use the law shown in **B.**

$9^{\frac{1}{2}}\cdot3^{\frac{1}{2}}= \\
(9\cdot3)^{\frac{1}{2}}=\\
27^{\frac{1}{2}}=\\
\boxed{\sqrt{27}}$In the last steps we performed the multiplication, and then used the law of defining the root as an exponent shown earlier in **A** __(in the opposite direction)__** **in order to return to the root notation.

__Therefore, the correct answer is answer C.__